Application of the TARCH Model for Stock Price Prediction: Evidence from PT Bank Rakyat Indonesia (BRI) Tbk - Putri Dina Sari; Faula Arina; Aulia Ikhsan; Isnaini Mahuda; Syarif Abdullah; Patricia Pingkan Kumenap; Regina Dwirahma Alisya (Theta: Journal of Statistics, 2025)
Stock price volatility is a crucial aspect in capital market analysis because it can influence investment decisions. The GARCH model is commonly used to model volatility, but this model assumes that positive and negative shocks affect volatility symmetrically. In practice, particularly in banking stocks, asymmetric effects are often observed, with negative shocks having a greater impact on volatility than positive shocks. To address this issue, this study uses the Threshold ARCH (TARCH) model, which is capable of capturing asymmetric effects. The research data consists of the daily closing prices of PT Bank Rakyat Indonesia (BRI) Tbk shares from January 2, 2015, to September 12, 2025. The results show that the TARCH model is more appropriate than the symmetric GARCH model, as the asymmetry coefficient is significant, indicating the presence of leverage in BRI shares. Therefore, the TARCH model can be used to forecast BRI stock volatility and provide more accurate information for investors and analysts in anticipating market risks.